THE FARMER-HERDER CONFLICTS AND THEIR EFFECT ON THE NIGERIAN ECONOMY: THE CONTRIBUTION OF TRADITIONAL LEADERS (MAIANGWAS AND ARDOS) - Danladi, Uhwe Shamaki (American Journals, 2025)
Nigeria's agricultural productivity has been severely hampered by ongoing conflicts between farmers and herders, which has had an adverse economic impact. Nigeria's economy and livelihoods depend heavily on agriculture, but these conflicts have hampered farming, decreased crop yields, and damaged farmlands and animals, worsening food insecurity and driving up food costs. These disturbances discourage investments in agriculture and reduce productivity and revenue generation, posing a further danger to economic stability. As a result, unemployment rises, leading job losses throughout agricultural value chains, farmers and herders to lose their sources of income, and rural-urban migration. By escalating competition for limited resources, rapid population increase and climate change exacerbate these conflicts. Droughts and desertification drive herders southward, creating conflict between farmers growing the same land and herders vying for water and grazing areas. This study's analytical framework is based on the environmental resource scarcity and frustration-aggression theories, and it uses secondary data. By giving them constitutional authority for mediation and reconciliation, the government should empower traditional leaders, especially Ardos and Maiangwas, according to the findings. Furthermore, promoting long-term conflict resolution will require treating farmers and herders fairly through subsidies and other types of aid, as well as including these leaders in the execution of policies.
Keywords: Farmer-Herder, Conflicts, Nigerian Economy, Traditional Leaders.